Gas-sensitive material for monitoring environment-friendly gas characteristic substance CO as well as preparation method and application of gas-sensitive material

By preparing MoS2/SnO2 composite materials with mesoporous hollow nanotube structure, the existing CO sensor devices are solved, and high selectivity and stability are achieved, and the decomposition component CO of environmentally friendly insulating gas is suitable.

CN119822402AActive Publication Date: 2025-04-15STATE GRID SICHUAN ELECTRIC POWER CORP ELECTRIC POWER RES INST

Patent Information

Application Number
CN202411776128.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-15
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing resistive sensors that monitor CO have problems with high device weight, low sensitivity, and stability and selectivity.

Method used

Ammonium fluoride was added to the mixed solution obtained by dissolving tin tetrachloride pentahydrate, sodium hydroxide and polyvinylpyrrolidone, and SnO2 nanoparticles were prepared after the reaction, and MoS2 nanosheet dispersion and SnO2 dispersion were mixed by ultrasonic to prepare MoS2/SnO2 composite material with mesoporous hollow nanotube structure.

Benefits of technology

This composite material has the advantages of low density, high pore volume, large specific surface area, and strong structural stability. When used to monitor CO, it can reduce the weight of the device, improve the selectivity and sensitivity to CO, and has good long-term stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822402A_ABST
    Figure CN119822402A_ABST
Patent Text Reader

Abstract

The invention discloses a gas-sensitive material for monitoring an environment-friendly gas characteristic substance CO as well as a preparation method and application thereof, and relates to the technical field of gas-sensitive materials. The preparation method comprises the following steps: dissolving tin tetrachloride pentahydrate, sodium hydroxide and polyvinylpyrrolidone, adding ammonium fluoride, reacting at 155-165 DEG C, drying the product, and calcining at 295-305 DEG C to obtain SnO2 nanoparticles; the preparation method comprises the following steps: performing ultrasonic mixing on SnO2 deionized water dispersion liquid and MoS2 nanosheet ethylene glycol dispersion liquid, and then drying to obtain the MoS2 / SnO2 composite material with a mesoporous hollow nanotube structure, and the volume ratio of ethylene glycol to deionized water is (0.9-1.1): 1. The MoS2 / SnO2 gas sensitive material has the advantages of low density, high pore volume, large specific surface area, high structural stability and the like. And when applied to a CO resistive sensor, the catalyst has good CO selectivity, high sensitivity and good long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas-sensitive materials, and in particular to a gas-sensitive material for monitoring an environmentally friendly gas characteristic substance CO, a preparation method and an application thereof. Background Art

[0002] SF6 is the most widely used insulating gas in the power industry, but due to its strong greenhouse effect, people have been looking for alternative gases in recent years, including C4F7N, C5F 10 O has attracted wide attention due to its good insulation performance and environmentally friendly nature. However, in actual application scenarios, some C4F7N, C5F 10 O gas will decompose to form a series of fluorocarbons. Due to the presence of trace amounts of water and oxygen in the equipment, these fluorocarbons will further react to form by-products, which will lead to a decrease in the insulation performance of the gas, causing electrical equipment failures and even threatening the stable operation of the power grid.

[0003] CO is environmentally friendly C4F7N, C5F 10 O mixed gas is one of the stable byproducts generated under fault conditions. Therefore, monitoring the generation of CO can diagnose the fault decomposition of insulating gas and provide timely warning to prevent further expansion of accidents. The traditional method of using GCMS to detect CO cannot meet the miniaturization and real-time nature of on-site detection due to its large footprint and cumbersome operation method. The low cost, low power consumption and small size of resistive sensors bring hope for the online monitoring of CO and are expected to meet the needs of daily real-time monitoring.

[0004] Gas-sensitive materials are the core of resistive gas sensors and are also the bottleneck for the practical application of such sensors at this stage. Existing resistive sensors for monitoring CO have the defects of high device weight, low sensitivity, and stability and selectivity that need to be improved. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0006] To this end, the first aspect of the present invention provides a method for preparing a gas-sensitive material for monitoring environmental gas characteristic CO, comprising: Dissolve tin tetrachloride pentahydrate, sodium hydroxide and polyvinyl pyrrolidone to obtain a clear mixed solution, add ammonium fluoride to the mixed solution, react at 155°C to 165°C for 23h to 25h, and then naturally cool to room temperature, wash the reaction product, dry it, and then calcine it at 295°C to 305°C to obtain SnO2 nanoparticles; The SnO2 nanoparticles are dispersed in deionized water to obtain a SnO2 dispersion, the MoS2 nanosheets are dispersed in ethylene glycol to obtain a MoS2 nanosheet dispersion, the SnO2 dispersion and the MoS2 nanosheet dispersion are ultrasonically mixed, and then dried to obtain a MoS2 / SnO2 composite material; wherein the volume ratio of the ethylene glycol to the deionized water is (0.9~1.1):1, and the microscopic morphology of the MoS2 / SnO2 composite material is a hollow nanotube structure with mesopores.

[0007] Furthermore, in the MoS2 / SnO2 composite material, the mass fraction of MoS2 is 1%~5%, and the mass fraction of SnO2 is 95%~99%.

[0008] Furthermore, in the ultrasonic mixing, the ultrasonic temperature is 80° C. to 120° C., and the ultrasonic time is 1 h to 2 h.

[0009] Furthermore, it also includes: dissolving the tin tetrachloride pentahydrate, the sodium hydroxide and the polyvinyl pyrrolidone in the ethanol aqueous solution, and stirring to obtain the clear mixed solution; wherein the mass ratio of the tin tetrachloride pentahydrate, the sodium hydroxide and the polyvinyl pyrrolidone is (3.5~3.7):(2.3~2.5):1, and the volume concentration of ethanol in the ethanol aqueous solution is 45%~55%.

[0010] Furthermore, the amount of ammonium fluoride added is 0.09wt%~0.11wt% of the mixed solution.

[0011] The second aspect of the present invention provides a gas-sensitive material for monitoring the environmental gas characteristic substance CO, which is the MoS2 / SnO2 composite material prepared by the above-mentioned preparation method.

[0012] A third aspect of the present invention provides an application of a gas-sensitive material for monitoring CO, a characteristic gas of environmental protection. The gas-sensitive material is used to prepare a resistive sensor for CO.

[0013] Furthermore, the CO resistance sensor is used to monitor the environmentally friendly insulating gas C4F7N and / or the environmentally friendly insulating gas C5F 10 The decomposition component of O is CO.

[0014] Furthermore, the method for preparing the resistive sensor of CO comprises: The MoS2 / SnO2 composite material is added to deionized water and ultrasonically dispersed to obtain a MoS2 / SnO2 suspension. The MoS2 / SnO2 suspension is evenly coated on the electrode surface of the CO resistive sensor and dried. The concentration of the MoS2 / SnO2 suspension is 14 mg / mL to 16 mg / mL.

[0015] Furthermore, the coating thickness of the MoS2 / SnO2 composite material is 40 μm to 60 μm.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: The preparation method of the gas-sensitive material for monitoring the characteristic gas CO provided by the present invention, on the one hand, the morphology of SnO2 nanoparticles is regulated by ammonium fluoride to obtain a single SnO2 nanoparticle with a particle size less than 40nm and stable existence; on the other hand, by controlling the volume ratio of deionized water in the SnO2 dispersion and ethylene glycol in the MoS2 dispersion, the optimal fusion effect of SnO2 nanoparticles and MoS2 nanosheets is obtained, and a MoS2 / SnO2 composite material with a mesoporous hollow nanotube structure is obtained. The composite material has the advantages of low density, high pore volume, large specific surface area, strong structural stability, etc. Used for monitoring environmental insulating gas C4F7N and / or environmental insulating gas C5F 10 The decomposition component of O, CO, is used in CO resistive sensors, which is beneficial to reducing the weight of the device and has good selectivity for CO, high sensitivity, and good long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the embodiments of the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0018] Figure 1a This is a SEM microscopic morphology of SnO2 prepared in Example 1 of the present invention (ammonium fluoride ratio 0.1wt%).

[0019] Figure 1b This is a SEM microscopic morphology of SnO2 prepared by adding 0.1wt% sodium citrate provided in an embodiment of the present invention.

[0020] Figure 1c This is a SEM microscopic morphology of SnO2 prepared by adding 0.1wt% sodium dodecyl sulfate provided in an embodiment of the present invention.

[0021] Figure 2a This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Example 1 of the present invention.

[0022] Figure 2b This is a SEM microscopic morphology of the MoS2 / SnO2 gas-sensitive material prepared with NMP as the MoS2 nanosheet dispersion solvent provided in an embodiment of the present invention.

[0023] Figure 2c This is a SEM microscopic morphology of the MoS2 / SnO2 gas-sensitive material prepared with DMF as the MoS2 nanosheet dispersion solvent provided in an embodiment of the present invention.

[0024] Figure 3a This is a SEM microscopic morphology image of SnO2 prepared in Comparative Example 1 of the present invention.

[0025] Figure 3b This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 1 of the present invention.

[0026] Figure 4a This is a SEM microscopic morphology image of SnO2 prepared in Comparative Example 2 of the present invention.

[0027] Figure 4b This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 2 of the present invention.

[0028] Figure 5 This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 3 of the present invention.

[0029] Figure 6 This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 4 of the present invention.

[0030] Figure 7 This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 5 of the present invention.

[0031] Figure 8 This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 6 of the present invention.

[0032] Fig. 9 This is a SEM microscopic morphology image of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 7 of the present invention.

[0033] Fig.10 This is the SEM micromorphology of the MoS2 / SnO2 gas-sensitive material prepared in Comparative Example 8 of the present invention.

[0034] Fig.11 The CO sensor prepared by using the MoS2 / SnO2 composite material of Example 1 for C5F 10 Response curves of different concentrations of CO, the characteristic decomposition component of O gas.

[0035] Fig.12 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 1 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0036] Fig.13 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 2 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0037] Fig.14 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 3 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0038] Fig.15 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 4 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0039] Fig.16 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 5 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0040] Fig.17 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 6 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0041] Fig.18 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 7 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0042] Fig.19 The CO sensor prepared by using the MoS2 / SnO2 composite material of Comparative Example 8 for C5F 10 Response curve of CO (50ppm), the characteristic decomposition component of O gas.

[0043] Fig. 20 The CO sensor prepared by using the MoS2 / SnO2 composite material of Example 1 for C5F 10 Schematic diagram of the selectivity of characteristic decomposition components of O gas.

[0044] Fig.21 The CO sensor prepared by using the MoS2 / SnO2 composite materials of Example 1 and Comparative Examples 1 to 8 for C5F 10 Long-term stability data of CO, a characteristic decomposition component of O gas. DETAILED DESCRIPTION

[0045] In order to better understand the above-mentioned technical scheme, the technical scheme of the embodiments of the present application is described in detail below through the accompanying drawings and specific embodiments. It should be understood that the embodiments of the present application and the specific features in the embodiments are detailed descriptions of the technical scheme of the embodiments of the present application, rather than limitations on the technical scheme of the present application. In the absence of conflict, the embodiments of the present application and the technical features in the embodiments may be combined with each other.

[0046] According to a first aspect of an embodiment of the present invention, there is provided a method for preparing a gas-sensitive material for monitoring an environmental gas characteristic substance CO, comprising: Dissolve tin tetrachloride pentahydrate, sodium hydroxide and polyvinyl pyrrolidone to obtain a clear mixed solution, add ammonium fluoride to the mixed solution, react at 155°C to 165°C for 23h to 25h, and then naturally cool to room temperature, wash the reaction product, dry it, and then calcine it at 295°C to 305°C to obtain SnO2 nanoparticles; The SnO2 nanoparticles are dispersed in deionized water to obtain a SnO2 dispersion, the MoS2 nanosheets are dispersed in ethylene glycol to obtain a MoS2 nanosheet dispersion, the SnO2 dispersion and the MoS2 nanosheet dispersion are ultrasonically mixed, and then dried to obtain a MoS2 / SnO2 composite material; wherein the volume ratio of the ethylene glycol to the deionized water is (0.9~1.1):1, and the microscopic morphology of the MoS2 / SnO2 composite material is a hollow nanotube structure with mesopores.

[0047] The method for preparing a gas-sensitive material for monitoring the characteristic gas CO of environmental protection provided in an embodiment of the present invention, on the one hand, regulates the morphology of SnO2 nanoparticles by ammonium fluoride to obtain stable single SnO2 nanoparticles with a particle size less than 40nm; on the other hand, by controlling the volume ratio of deionized water in the SnO2 dispersion and ethylene glycol in the MoS2 dispersion, the optimal fusion effect of SnO2 nanoparticles and MoS2 nanosheets is obtained, and a MoS2 / SnO2 composite material with a hollow nanotube structure with mesopores (the nanoparticles are aggregated on the tube wall of the hollow nanotube, and mesopores exist on the tube wall) is obtained. The composite material has the advantages of low density, high pore volume, large specific surface area, strong structural stability, etc.

[0048] In a feasible embodiment, in the MoS2 / SnO2 composite material, the mass fraction of MoS2 is 1%~5%, and the mass fraction of SnO2 is 95%~99%.

[0049] In a feasible implementation manner, the ultrasonic mixing is performed at an ultrasonic temperature of 80° C. to 120° C. and for an ultrasonic time of 1 h to 2 h.

[0050] Specifically, we optimized the ultrasonic temperature and time for the fusion of MoS2 and SnO2, and found that the ultrasonic temperature is 80℃~120℃. Temperatures below 80℃ or above 120℃ cannot be effectively fused, and temperatures above 120℃ are at risk of boiling. The preferred ultrasonic temperature is 90℃~110℃. The ultrasonic time is 1h~2h. If the time is less than 1h, the fusion of MoS2 and SnO2 is not completed. Too long a time is not economical and has no obvious effect on increasing the yield. The preferred ultrasonic time is 60min~70min.

[0051] In a feasible embodiment, the method further comprises: dissolving the tin tetrachloride pentahydrate, the sodium hydroxide and the polyvinyl pyrrolidone in an ethanol aqueous solution, and stirring to obtain the clear mixed solution; wherein the mass ratio of the tin tetrachloride pentahydrate, the sodium hydroxide and the polyvinyl pyrrolidone is (3.5-3.7): (2.3-2.5): 1, and the volume concentration of ethanol in the ethanol aqueous solution is 45%-55%.

[0052] In a feasible implementation manner, the amount of ammonium fluoride added is 0.09wt%~0.11wt% of the mixed solution.

[0053] Specifically, we found in our experiments that by controlling the amount of ammonium fluoride added to the mixed solution, the morphology of SnO2 can be regulated. When the amount of ammonium fluoride added is 0.09wt%~0.11wt% of the mixed solution, the prepared SnO2 can form stable single particles with a particle size of less than 40nm and high yield.

[0054] According to a second aspect of an embodiment of the present invention, a gas-sensitive material for monitoring the characteristic environmental gas CO is provided, which is the MoS2 / SnO2 composite material prepared by the above-mentioned preparation method.

[0055] According to a third aspect of the embodiments of the present invention, there is provided an application of a gas-sensitive material for monitoring CO, a characteristic gas of environmental protection. The gas-sensitive material is used to prepare a resistive sensor for CO.

[0056] In a feasible implementation manner, the CO resistive sensor is used to monitor the environmentally friendly insulating gas C4F7N and / or the environmentally friendly insulating gas C5F 10 The decomposition component of O is CO.

[0057] The detection principle of MoS2 / SnO2 composite materials for CO is: When the MoS2 / SnO2 composite material is exposed to air, the surface of the gas-sensitive material will absorb O2 molecules in the air and transport electrons to form oxygen anions:

[0058]

[0059] This will lead to the formation of a depletion layer and a high resistance state on the surface of the gas-sensitive material. When the reducing gas CO is introduced, the CO molecules on the surface of the sensing material will react with O2:

[0060] During this reaction, CO will release electrons to the gas-sensitive material, causing the resistance to decrease.

[0061] In a feasible implementation manner, the method for preparing the resistive sensor of CO comprises: The MoS2 / SnO2 composite material is added to deionized water and ultrasonically dispersed to obtain a MoS2 / SnO2 suspension. The MoS2 / SnO2 suspension is evenly coated on the electrode surface of the CO resistive sensor and dried. The concentration of the MoS2 / SnO2 suspension is 14 mg / mL to 16 mg / mL.

[0062] Specifically, we found through experiments that the concentration of MoS2 / SnO2 suspension is 14mg / mL~16mg / mL, which is suitable for coating and drying. If the concentration is too low, it will result in too much suspension required for coating, which is not conducive to subsequent drying; if the concentration is too high, the suspension will be dense, which is not conducive to uniform coating.

[0063] In a feasible implementation manner, the coating thickness of the MoS2 / SnO2 composite material is 40 μm to 60 μm.

[0064] Specifically, a coating thickness below 40 μm will result in poor material strength and easy breakage, and a coating thickness above 60 μm will result in the bottom layer material being tightly bonded to the electrode, but the surface layer material being easy to fall off.

[0065] The present invention is described below in conjunction with specific experimental processes and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0066] 1. Investigation of morphology modifiers in the preparation of SnO2 nanoparticles We selected ammonium fluoride, sodium citrate and sodium dodecyl sulfate as morphology regulators for the preparation of SnO2 nanoparticles for experiments, as follows.

[0067] (1) Ammonium fluoride The preparation of SnO2 nanoparticles includes the following steps: dissolving 0.9g of tin tetrachloride pentahydrate, 0.6g of sodium hydroxide and 0.25g of polyvinyl pyrrolidone in 20ml of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 1:1), stirring for 1h to obtain a clear mixture, adding 0.1wt% of ammonium fluoride thereto, reacting at 160°C for 24h, cooling naturally to room temperature, washing the reaction product with deionized water and ethanol, drying at 80°C for 12h, and calcining at 300°C for 1h to obtain SnO2 nanoparticles, such as Figure 1a As shown, by adding ammonium fluoride, SnO2 nanoparticles were successfully synthesized to form stable single particles with higher yield.

[0068] (2) Sodium citrate The preparation of SnO2 nanoparticles includes the following steps: dissolving 0.9g of tin tetrachloride pentahydrate, 0.6g of sodium hydroxide and 0.25g of polyvinyl pyrrolidone in 20ml of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 1:1), stirring for 1h to obtain a clear mixture, adding 0.1wt% of sodium citrate thereto, reacting at 160°C for 24h, cooling naturally to room temperature, washing the reaction product with deionized water and ethanol, drying at 80°C for 12h, and calcining at 300°C for 1h to obtain SnO2 nanoparticles, such as Figure 1b As shown, with the addition of sodium citrate, the synthesis of SnO2 nanoparticles failed and exhibited a cheese-like morphology.

[0069] (3) Sodium dodecyl sulfate The preparation of SnO2 nanoparticles includes the following steps: dissolving 0.9g of tin tetrachloride pentahydrate, 0.6g of sodium hydroxide and 0.25g of polyvinyl pyrrolidone in 20ml of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 1:1), stirring for 1h to obtain a clear mixture, adding 0.1wt% of sodium dodecyl sulfate thereto, reacting at 160°C for 24h, cooling naturally to room temperature, washing the reaction product with deionized water and ethanol, drying at 80°C for 12h, and calcining at 300°C for 1h to obtain SnO2 nanoparticles, such as Figure 1c As shown, when sodium dodecyl sulfate was added, the synthesis of SnO2 nanoparticles failed, and a large irregular plate-like finished product like a turtle's back appeared.

[0070] Therefore, the present application selects ammonium fluoride as the morphology regulator for preparing SnO2 nanoparticles.

[0071] 2. Investigation of MoS2 nanosheet dispersion solvents We selected ethylene glycol, N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF) as the dispersing solvents of MoS2 nanosheets, respectively, and fused them with the aqueous dispersion of SnO2. The preparation method of SnO2 nanoparticles is as follows: 0.9g of tin tetrachloride pentahydrate, 0.6g of sodium hydroxide and 0.25g of polyvinylpyrrolidone are dissolved in 20ml of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 1:1), stirred for 1h to obtain a clear mixture, and then 0.1wt% of ammonium fluoride is added thereto, reacted at 160°C for 24h, cooled naturally to room temperature, and then the reaction product was washed with deionized water and ethanol, dried at 80°C for 12h, and calcined at 300°C for 1h to obtain SnO2 nanoparticles, such as Figure 1a shown.

[0072] (1) Ethylene glycol 99 mg of the obtained SnO2 nanoparticles were dispersed in 5 mL of deionized water, 1 mg of MoS2 nanosheets were dispersed in 5 mL of ethylene glycol, and the volume ratio of ethylene glycol to deionized water was 1:1. The MoS2 nanosheet mixture was added to the SnO2 mixture, and after ultrasonication at 100 °C for 1 h, the mixture was collected and dried in an oven at 80 °C for 12 h to obtain a MoS2 / SnO2 composite material, such as Figure 2a As shown, when the volume ratio of ethylene glycol to deionized water is 1:1, it can be found that SnO2 and MoS2 are perfectly fused to form hollow nanotubes with mesopores.

[0073] (2) NMP 99 mg of the obtained SnO2 nanoparticles were dispersed in 5 mL of deionized water, 1 mg of MoS2 nanosheets were dispersed in 5 mL of NMP, the volume ratio of ethylene glycol to deionized water was 1:1, the MoS2 nanosheet mixture was added to the SnO2 mixture, and after ultrasonication at 100 °C for 1 h, the mixture was collected and dried in an oven at 80 °C for 12 h to obtain a MoS2 / SnO2 composite material, such as Figure 2b As shown, SnO2 and MoS2 cannot be effectively fused.

[0074] (3) DMF 99 mg of the obtained SnO2 nanoparticles were dispersed in 5 mL of deionized water, 1 mg of MoS2 nanosheets were dispersed in 5 mL of DMF, the volume ratio of ethylene glycol to deionized water was 1:1, the MoS2 nanosheet mixture was added to the SnO2 mixture, and after ultrasonication at 100 °C for 1 h, the mixture was collected and dried in an oven at 80 °C for 12 h to obtain a MoS2 / SnO2 composite material, such as Figure 2c As shown, SnO2 and MoS2 were severely dissolved and lost their original morphology.

[0075] Therefore, this application selects ethylene glycol as the MoS2 nanosheet dispersion solvent.

[0076] The dosage of ammonium fluoride and ethylene glycol is further investigated below. Example 1 and Comparative Examples 1-8 We investigated the addition ratio of ammonium fluoride in step S1 and the volume ratio of ethylene glycol to deionized water in step S2, as shown in Table 1 for details.

[0077] Table 1

[0078] Example 1 A method for preparing a gas-sensitive material for monitoring environmental gas characteristic substance CO comprises the following steps: S1. Dissolve 0.9 g of tin tetrachloride pentahydrate, 0.6 g of sodium hydroxide and 0.25 g of polyvinyl pyrrolidone in 20 ml of ethanol aqueous solution (the volume ratio of ethanol to deionized water is 1:1), stir for 1 hour to obtain a clear mixture, add 0.1 wt% of ammonium fluoride thereto, react at 160 ° C for 24 hours, cool naturally to room temperature, wash the reaction product with deionized water and ethanol, dry at 80 ° C for 12 hours, and calcine at 300 ° C for 1 hour to obtain SnO2 nanoparticles.

[0079] S2. Disperse 99 mg of the obtained SnO2 nanoparticles in 5 mL of deionized water, disperse 1 mg of MoS2 nanosheets in 5 mL of ethylene glycol, the volume ratio of ethylene glycol to deionized water is 1:1, add the MoS2 nanosheet mixture to the SnO2 mixture, ultrasonicate at 100 °C for 1 h, collect the mixture and dry it in an oven at 80 °C for 12 h to obtain a MoS2 / SnO2 composite material (MoS2 mass proportion is 1%).

[0080] like Figure 1a As shown in Figure 1, the SnO2 material prepared in Example 1 can form stable single particles with high yield. The characterization results of the MoS2 / SnO2 composite material prepared in Example 1 are shown in Figure 1. Figure 2a As shown, it can be seen that the MoS2 / SnO2 composite material prepared in Example 1 is fused to become hollow nanotubes with mesopores. This is because 0.1wt% of ammonium fluoride is added in step S1 of Example 1, and ethylene glycol and deionized water are added in a volume ratio of 1:1 in step S2. The two synergistically change the microscopic morphology of the material.

[0081] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S1, 0.05 wt % of ammonium fluoride is added thereto. Step S2 is the same as Example 1.

[0082] The SnO2 nanoparticles prepared in Comparative Example 1 are as follows Figure 3a As shown in FIG. 1 , when half the amount of ammonium fluoride in Example 1 is added, the SnO2 material cannot form stable single particles, and the yield is lower than that in Example 1. The MoS2 / SnO2 composite material prepared in Comparative Example 1 is as follows Figure 3bAs shown, half the amount of ammonium fluoride cannot synthesize shaped SnO2, and the MoS2 / SnO2 composite material does not change significantly, but filaments begin to appear in the amorphous material.

[0083] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step S1, 0.2 wt % of ammonium fluoride is added thereto. Step S2 is the same as Example 1.

[0084] Comparative Example 2: SnO2 nanoparticles prepared as Figure 4a As shown, when twice the amount of ammonium fluoride as in Example 1 is added, the edges of the SnO2 particles are etched, and the yield is the same as in Example 1. The MoS2 / SnO2 composite material prepared in Comparative Example 2 is as follows Figure 4b As shown, due to the etching of the edges of the SnO2 particles (pellets), the spherical shells of the resulting MoS2 / SnO2 composite material particles (pellets) grew spherical protrusions.

[0085] Comparative Example 3 The difference between Comparative Example 3 and Comparative Example 1 is that in step S2, 99 mg of the obtained SnO2 nanoparticles are dispersed in 10 mL of deionized water, and 1 mg of MoS2 nanosheets are dispersed in 5 mL of ethylene glycol, and the volume ratio of ethylene glycol to deionized water is 1:2.

[0086] The MoS2 / SnO2 composite material prepared in Comparative Example 3 is as follows Figure 5 As shown, it is still an amorphous substance.

[0087] Comparative Example 4 The difference between Comparative Example 4 and Comparative Example 1 is that in step S2, 99 mg of the obtained SnO2 nanoparticles are dispersed in 2.5 mL of deionized water, and 1 mg of MoS2 nanosheets are dispersed in 5 mL of ethylene glycol, and the volume ratio of ethylene glycol to deionized water is 2:1.

[0088] The MoS2 / SnO2 composite material prepared in Comparative Example 4 is as follows Figure 6 As shown in the figure, the morphology of MoS2 / SnO2 composite material changes slightly with the increase of ethylene glycol dosage, and more filaments appear in the amorphous material.

[0089] Comparative Example 5 Step S1 of Comparative Example 5 is the same as that of Example 1. The difference between Comparative Example 5 and Example 1 is that in step S2, 99 mg of the obtained SnO2 nanoparticles are dispersed in 10 mL of deionized water, and 1 mg of MoS2 nanosheets are dispersed in 5 mL of ethylene glycol, and the volume ratio of ethylene glycol to deionized water is 1:2.

[0090] The MoS2 / SnO2 composite material prepared in Comparative Example 5 is as follows Figure 7 As shown, it can be found that the fusion is incomplete.

[0091] Comparative Example 6 Step S1 of Comparative Example 6 is the same as that of Example 1. The difference between Comparative Example 6 and Example 1 is that in step S2, 99 mg of the obtained SnO2 nanoparticles are dispersed in 2.5 mL of deionized water, and 1 mg of MoS2 nanosheets are dispersed in 5 mL of ethylene glycol, and the volume ratio of ethylene glycol to deionized water is 2:1.

[0092] The MoS2 / SnO2 composite material prepared in Comparative Example 6 is as follows Figure 8 As shown, it can be found that the nanotubes are too fused, the mesoporous morphology on the nanotubes is lost, and the nanotubes are stacked too densely to become thin solid tubes. This morphology is not conducive to increasing the specific surface area.

[0093] Comparative Example 7 The difference between Comparative Example 7 and Comparative Example 5 is that in step S1, 0.2 wt % of ammonium fluoride is added thereto.

[0094] The MoS2 / SnO2 composite material prepared in Comparative Example 7 is as follows Fig. 9 As shown, 0.2wt% of ammonium fluoride causes excessive etching of the spheres, and the subsequent volume ratio of ethylene glycol to deionized water is 1:2, causing the spheres to break into spherical shells.

[0095] Comparative Example 8 The difference between Comparative Example 8 and Comparative Example 6 is that in step S1, 0.2 wt % of ammonium fluoride is added thereto.

[0096] The MoS2 / SnO2 composite material prepared in Comparative Example 8 is as follows Fig.10 As shown, the ammonium fluoride ratio of 0.2wt% leads to excessive etching of the spheres, and the subsequent volume ratio of ethylene glycol to deionized water is 2:1, which leads to an increase in the degree of fragmentation of the spheres into spherical shells, and the fragmented materials aggregate into clusters.

[0097] Performance Testing The performance of the CO sensors prepared in Example 1 and Comparative Examples 1 to 8 was tested.

[0098] 1. Sensitivity The response of the sensor is defined by the ratio of Ra and Rg: (12) Where Ra is the resistance of the sensor in air and Rg is the resistance of the sensor in the target gas. The response time is defined as the time required to obtain 90% of the change in the total resistance of the gas sensor during adsorption, and in the case of desorption, it is defined as the recovery time.

[0099] Fig.11 The CO sensor prepared in Example 1 is C5F 10Response curves of different concentrations of CO, the characteristic decomposition component of O gas. It can be seen that the prepared CO sensor has a response height of 1.18 for 50ppmCO, and the response time and recovery time are 34s and 28s respectively.

[0100] Fig.12 The CO sensor prepared in Comparative Example 1 is C5F 10 The response curve of CO (50ppm), a characteristic decomposition component of O gas, shows that the response height of the CO sensor prepared in Comparative Example 1 to 50ppm CO is 1 (that is, no response, and the sensor resistance value only fluctuates near the baseline), so there is no response time and recovery time.

[0101] Fig.13 The CO sensor prepared in Comparative Example 2 is C5F 10 The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the response height of the CO sensor prepared in Comparative Example 2 to 50 ppm CO is 1.05, and the response time and recovery time are 54 s and 352 s, respectively.

[0102] Fig.14 The CO sensor prepared in Comparative Example 3 is C5F 10 The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the response height of the CO sensor prepared in Comparative Example 3 to 50 ppm CO is 1 (that is, no response, and the sensor resistance value only fluctuates near the baseline), so there is no response time and recovery time.

[0103] Fig.15 The CO sensor prepared in Comparative Example 4 is C5F 10 The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the response height of the CO sensor prepared in Comparative Example 4 to 50 ppm CO is 1 (that is, no response, and the sensor resistance value only fluctuates near the baseline), so there is no response time and recovery time.

[0104] Fig.16 The CO sensor prepared in Comparative Example 5 is C5F 10 The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the CO sensor prepared in Comparative Example 5 has a response height of 1.1 to 50 ppm CO, and the response time and recovery time are 44 s and 40 s, respectively.

[0105] Fig.17 The CO sensor prepared in Comparative Example 6 is C5F 10The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the response height of the CO sensor prepared in Comparative Example 6 to 50 ppm CO is 1.08, and the response time and recovery time are 26 s and 22 s, respectively.

[0106] Fig.18 The CO sensor prepared in Comparative Example 7 is C5F 10 The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the response height of the CO sensor prepared in Comparative Example 7 to 50 ppm CO is 1.05, and the response time and recovery time are 47 s and 431 s, respectively.

[0107] Fig.19 The CO sensor prepared in Comparative Example 8 is C5F 10 The response curve of CO (50 ppm), a characteristic decomposition component of O gas, shows that the CO sensor prepared in Comparative Example 8 has a response height of 1.03 to 50 ppm CO, and the response time and recovery time are 68 s and 297 s, respectively.

[0108] By comparison, the CO sensor prepared in Example 1 of the present invention has better sensitivity and shorter response and recovery time, indicating that the CO sensor prepared by the method of the present invention can effectively improve the sensitivity of the sensor and reduce the response and recovery time, proving the effect of ammonium fluoride and ethylene glycol on the micromorphology of the material, and the hollow tubular structure enhances the sensing performance.

[0109] 2. Selectivity The selectivity of a sensor refers to the ability of a gas sensor to resist interference from the target gas under the same test conditions.

[0110] Fig. 20 The CO sensor prepared in Example 1 of the present invention is C5F 10 Schematic diagram of the selectivity of characteristic decomposition components of O gas, from Fig. 20 As you can see, for C5F 10 The test results of the characteristic decomposition of each component of O gas show that the sensor prepared in Example 1 of the present invention has the highest response height to CO and has good selectivity.

[0111] 3. Stability The stability of gas-sensitive materials reflects the stability of the sensor's detection ability during long-term use, which can also be called the life of the sensor. Fig.21 The CO sensor prepared in Example 1 and Comparative Examples 1 to 8 of the present invention is C5F 10 The long-term stability data of CO, a characteristic decomposition component of O gas, from Fig.21It can be concluded that the response height of the CO sensor prepared in Example 1 of the present invention to CO remains basically unchanged within one month, indicating that the CO sensor prepared by the method of the present invention has good long-term stability; while the response height of the CO sensors prepared in Comparative Examples 1 to Comparative Examples 8 to CO begins to decrease after half a month, and the long-term stability is poor.

[0112] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A method for preparing a gas-sensitive material for monitoring environmental gas characteristic CO, characterized in that: include: Dissolve tin tetrachloride pentahydrate, sodium hydroxide and polyvinyl pyrrolidone to obtain a clear mixed solution, add ammonium fluoride to the mixed solution, react at 155°C to 165°C for 23h to 25h, and then naturally cool to room temperature, wash the reaction product, dry it, and then calcine it at 295°C to 305°C to obtain SnO2 nanoparticles; The SnO2 nanoparticles are dispersed in deionized water to obtain a SnO2 dispersion, the MoS2 nanosheets are dispersed in ethylene glycol to obtain a MoS2 nanosheet dispersion, the SnO2 dispersion and the MoS2 nanosheet dispersion are ultrasonically mixed, and then dried to obtain a MoS2 / SnO2 composite material; wherein the volume ratio of the ethylene glycol to the deionized water is (0.9~1.1):1, and the microscopic morphology of the MoS2 / SnO2 composite material is a hollow nanotube structure with mesopores.

2. The method for preparing a gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 1, characterized in that: In the MoS2 / SnO2 composite material, the mass fraction of MoS2 is 1% to 5%, and the mass fraction of SnO2 is 95% to 99%.

3. The method for preparing a gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 2, characterized in that: The ultrasonic mixing has an ultrasonic temperature of 80° C. to 120° C. and an ultrasonic time of 1 h to 2 h.

4. The method for preparing a gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 1 or 3, characterized in that: Also includes: The tin tetrachloride pentahydrate, the sodium hydroxide and the polyvinyl pyrrolidone are dissolved in an ethanol aqueous solution and stirred to obtain the clear mixed solution; wherein the mass ratio of the tin tetrachloride pentahydrate, the sodium hydroxide and the polyvinyl pyrrolidone is (3.5-3.7):(2.3-2.5):1, and the volume concentration of ethanol in the ethanol aqueous solution is 45%-55%.

5. The method for preparing a gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 4, characterized in that: The amount of ammonium fluoride added is 0.09wt%~0.11wt% of the mixed solution.

6. A gas-sensitive material for monitoring the environmental gas characteristic substance CO, characterized in that: It is the MoS2 / SnO2 composite material prepared by the preparation method described in any one of claims 1 to 5.

7. An application of a gas-sensitive material for monitoring environmental gas characteristic CO, characterized in that: The gas-sensitive material described in claim 6 is used to prepare a resistive sensor for CO.

8. The use of the gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 7, characterized in that: The CO resistive sensor is used to monitor environmentally friendly insulating gas C4F7N and / or environmentally friendly insulating gas C5F 10 The decomposition component of O is CO.

9. The use of the gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 7, characterized in that: The method for preparing the resistive sensor of CO comprises: The MoS2 / SnO2 composite material is added to deionized water and ultrasonically dispersed to obtain a MoS2 / SnO2 suspension. The MoS2 / SnO2 suspension is evenly coated on the electrode surface of the CO resistive sensor and dried. The concentration of the MoS2 / SnO2 suspension is 14 mg / mL to 16 mg / mL.

10. The use of the gas-sensitive material for monitoring the environmental gas characteristic substance CO according to claim 9, characterized in that: The coating thickness of the MoS2 / SnO2 composite material is 40 μm to 60 μm.

Citation Information

Patent Citations

  • Preparation method of doped modified tin dioxide used for glass thermal-insulation coating

    CN107974105A

  • Preparation method and application of polypeptide / MoS2 / SnO2 composite material

    CN114002269A

  • Fluorine-doped tin oxide transparent conductive film glass and method of fabricating the same

    US20090053511A1

  • Electrode mixture, electrode, and nonaqueous electrolyte secondary cell

    US20110256442A1

Cited By

  • Carbon monoxide gas sensor as well as preparation method and application thereof

    CN120948566A

  • Application of PES / UiO-66 composite membrane as gas sensitive material to detection of characteristic decomposition component CO of C4F7N / CO2 mixed gas

    CN121612941A

  • Application of PES / UiO-66 composite membrane in detection of characteristic decomposition component CO of C4F7N / CO2 mixed gas as gas sensitive material

    CN121612941B